OPTIMALISASI HASIL PROSES WIRE-CUT EDM DENGAN METODE PRINCIPAL COMPONENT ANALYSIS (PCA) - Mulyadi Mulyadi; Agus Puji Suryanto (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
Some of the desired performance of the machining process Wire-Cut Electric Discharge Machining CV. Catur Prasetya Packindo is rate workmanship short and surface roughness of lower cutting. The problem is how to manage the performance of process variables that can be optimized simultaneously.To perform the optimization process must first be determined the relationship between the performance of the machining process wire cut to variable Interpulse process, Electric current, Wire Speed and Variable Frequency with PCA method.The relationship model is obtained from experiments carried out by the draft Central Composite Design (CCD) .Optimasi response is made with the help of Minitab software 16. The data used in this study are primary data obtained from experimental results. Variable response to be observed include material processing rate (MRR), cutting time, cutting width, surface roughness (Ra), then a constant variable is a variable process that is not examined. These variables are maintained during the experimental process so it does not affect the results.In order to estimate the contribution of the influence of each factor on the response so that the accuracy of the model used can be determined, then used analysis of variance (ANOVA) which is a quantitative calculation techniques. To determine the extent to which the accuracy of the values that are statistically stationary generate value optimal response, then validated against the values stationary.To prove the presence or absence of a deviation between the results of the validation test will be conducted on the calculation of the sample one for setting optimum parameters for a confirmation test. Optimization of the cutting material samples SKD-11 is around 15 mm to produce the shortest time 5 minutes 21 seconds, cutting the narrowest width of 0.481 mm, the minimum surface roughness in Ra of 6.0 μm and maximum MRR was 13,93 . The fourth value is the best setting parameters obtained from the optimization by setting a value Pulse interval of 9, electric current of 10 Wire speed by 5 and variable frequency by 80.